33 GHz Overmoded Bulk Acoustic Resonator - Schaffer, Zachary; Simeoni, Pietro; Piazza, Gianluca (IEEE microwave and wireless components letters, 2022)
In this work, we present a new class of thickness extensional microelectromechanical resonator, the overmoded bulk acoustic resonator (OBAR) for filtering applications in the 5G millimeter wave (mm-wave) spectrum. This resonator operates in a second overtone thickness mode with approximately equal thickness electrodes and piezoelectric layer so that acoustic energy is distributed evenly between the different layers. Compared to a fundamental mode at a fixed frequency, the OBAR possess a 3× thicker piezo layer and 5- 10× thicker metal electrodes, enabling manufacturable 30-60 GHz devices. We demonstrate the OBAR experimentally through fabrication of a Pt-AlN-Al device with electromechanical-coupling coefficient ( k_{t}^{2} ) of 1.7%, and series resonance quality factor ( Q_{s} ) of 110 at 33 GHz.